A Review of the Hydrochemistry of a Deep Sedimentary Aquifer and Its Consequences for Geothermal Operation: Klaipeda, Lithuania. (9th April 2019) - Brehme, Maren; Nowak, Kerstin; Banks, David; Petrauskas, Sigitas; Valickas, Robertas; Bauer, Klaus; Burnside, Neil; Boyce, Adrian
Abstract : The Klaipeda Geothermal Demonstration Plant (KGDP), Lithuania, exploits a hypersaline sodium-chloride (salinity c. 90 g/L) groundwater from a 1100 m deep Devonian sandstone/siltstone reservoir. The hydrogen and oxygen stable isotope composition is relatively undepleted (δ 18 O = c . -4.5‰), while the δ 34 S is relatively "heavy" at +18.9‰. Hydrochemical and isotopic data support the existing hypothesis that the groundwater is dominated by a hypersaline brine derived from evapoconcentrated seawater, modified by water-rock interaction and admixed with smaller quantities of more recent glacial meltwater and/or interglacial recharge. The injectivity of the two injection boreholes has declined dramatically during the operational lifetime of the KGDP. Initially, precipitation of crystalline gypsum led to a program of rehabilitation and the introduction of sodium polyphosphonate dosing of the abstracted brine, which has prevented visible gypsum precipitation but has failed to halt the injectivity decline. While physical or bacteriological causes of clogging are plausible, evidence suggests that chemical causes cannot be excluded. Gypsum and barite precipitation could still occur in the formation, as could clogging with iron/manganese oxyhydroxides. One can also speculate that inhibitor dosing could cause clogging of pore throats with needles of calcium polyphosphonate precipitate.